The Maghreb issue in the interests of the Tunisian youth movement 1911/1920 - djemaa, rebai; Būṭībī , Muḥammad (The Algerian Historical Journal, 2026)
The study deals with the Tunisian Youth Movement, which was founded in 1906, as a pioneering movement in the Arab Maghreb during the French colonial period. This made them change his reformist tone, which turned to the political side, taking advantage of German propaganda in North Africa against the Allied countries. What is the extent of the contribution of the Tunisian youth movement to Maghreb issues during the period between 1911/1920? In what embodied the Maghreb struggle?